SO029FIRST YEAR RENAL OUTCOME OF TRANSPLANTATIONS OF KIDNEYS FROM HEPATITIS C INFECTED DONORS TO HEPATITIS C NEGATIVE RECIPIENTS. (6th June 2020) - Molnar, Miklos Zsolt; Talwar, Manish; Balaraman, Vasanthi; Bhalla, Anshul; Azhar, Ambreen; Yazawa, Masahiko; Tsujita, Makoto; Podila, Pradeep; Nair, Satheesh; Eason, James
Abstract: Background and Aims: Transplant centers in US are increasingly willing to transplant kidneys from hepatitis C infected donors to hepatitis C negative recipients. Long-term renal outcome data from non-prophylactic treatment approach outside clinical trials is missing. Method: We compared kidney graft function of 132 hepatitis C negative recipients, who received HCV infected (NAT+ and antibody+/-; HCV+) versus HCV negative (NAT- and antibody-; HCV-) in 2018, in a single center, retrospective, observational study. Categorical variables were compared using χ 2 tests and continuous variables were compared using t-tests or Mann–Whitney U-tests, as appropriate. Linear regression was applied to assess independent association between graft function and HCV viremic status. Results: The mean±SD age of recipients was 52±11 years, 44% were female, 20% and 79% of recipients were Caucasian and African-American, respectively. Baseline characteristics were similar between HCV+ vs HCV- groups, except dialysis duration, donors race, KDPI and cold ischemic time (Table). The DGF rate, estimated GFRs at post-transplant 3, 6, 9 and 12 months was similar between HCV+ and HCV- groups (Table). HCV viremic status was not a predictor of 3, 6, 9 and 12 months eGFR in our unadjusted model and after adjustment for donor and recipient characteristics. Conclusion: Recipients of HCV-viremic kidneys have similar renal allograft function in the first year after transplantation compared to those who received from HCV-non-viremic kidneys.